Longitudinal Increases in Parent–Child Relationship Quality and Sensation Seeking Interact to Increase Risk-Taking During the College Transition. Issue 1 (February 2018) - Guassi Moreira, João F.; Telzer, Eva H.
We tested two competing predictions of whether changes in parent–child relationship quality buffer or exacerbate the association between sensation-seeking and risk-taking behaviors as individuals gain more independence during the high school–college transition. In the current longitudinal study, 287 participants completed self-report measures of sensation seeking, risk-taking, and parent–child relationship quality with their parents prior to starting college and again during their first semester. Overall, students displayed increases in risky behaviors, which were predicted by sensation seeking. Changes in relationship quality moderated the association between sensation seeking and risk-taking, such that sensation seeking predicted higher risk-taking behaviors during the first semester of college, but only for those who reported increases in relationship quality across the college transition. These results suggest that increased relationship quality may have an inadvertent spillover effect by interacting with sensation seeking to increase risky behaviors.